Numerical study on bearing behaviour and design of aluminium sub-heads in façade systems. (November 2021) - Akbari, Masoumeh; Gunalan, Shanmuganathan; Talebian, Nima; Gilbert, Benoit P.; Guan, Hong
Abstract: A sub-head refers to the horizontal member at the top of an aluminium window wall system. Under wind load, bearing failure of the aluminium sub-head (ASH) flange due to its long length is a common failure mode, being subjected to high concentrated load transferred from the vertical members (mullions). The bearing behaviour of ASH sections was previously investigated experimentally by the authors and suitable equations (DRA I ) were proposed to predict the bearing capacities. These design rules were manufacturer and product specific and only applicable for sections considered in the test plan. To address these limitations, the present study further investigates the behaviour and design of ASH sections through non-linear static analyses using ABAQUS, based on implicit integration schemes. The effects of mesh size, element type, and loading plates on the bearing behaviour of ASH section under different loading and boundary conditions was addressed. The finite element models were validated against the test results in terms of ultimate loads, load–displacement curves and failure modes, and the validated model was then used to perform an extensive parametric study. A broad range of ASH sections covering flange widths ranging from 40 to 100 mm, thicknesses varying between 2 and 4 mm, bearing widths ranging from 50 to 150 mm, and six engagement lengths (5 to 30 mm) was considered in the parametric study. It should be noted that the ultimate loads obtained from the parametric study are not product nor manufacturer specific. Since no aluminium design rules exist to predict the bearing capacities of ASH sections, the accuracy of the current cold-formed steel design rules (DRSs) and that of DRA I were assessed. Both DRSs and DRA I were found not to be suitable for ASH sections in window walls, hence appropriate modifications were made in this study and the proposed design rules (DRA P ) predicted accurate bearing capacities which agreed well with the numerical results. Highlights: Numerically investigated the bearing behaviour of aluminium sub-heads in façade systems. Considered various section geometries, bearing widths, loading and boundary conditions. The finite element models were validated against the previous test results and extensive parametric study were performed. Current cold-formed steel design equations were not suitable for aluminium sub-heads in window walls. New design rules were proposed for aluminium sub-heads based on the numerical results.